The effects of seed ingestion by livestock, dung fertilization, trampling, grass competition and fire on seedling establishment of two woody plant species. - Julius Tjelele; David Ward; Luthando Dziba (PLoS ONE)
The increasing rate of woody plant encroachment in grasslands or savannas remains a challenge to livestock farmers. The causes and control measures of woody plant encroachment are of common interest, especially where it negatively affects the objectives of an agricultural enterprise. The objectives of this study were to determine the effects of gut passage (goats, cattle), dung (nutrients), fire, grass competition and trampling on establishment of A. nilotica and D. cinerea seedlings. Germination trials were subjected to the following treatments: 1) seed passage through the gut of cattle and goats and unpassed/ untreated seeds (i.e. not ingested), 2) dung and control (no dung), 3) grass and control (mowed grass), 4) fire and control (no fire), 5) trampling and control (no trampling). The interaction of animal species, grass and fire had an effect on seedling recruitment (P < 0.0052). Seeds retrieved from goats and planted with no grass and with fire (6.81% ± 0.33) had a significant effect on seedling recruitment than seeds retrieved from goats and planted with grass and no fire (2.98% ± 0.33). Significantly more D. cinerea and A. nilotica seeds germinated following seed ingestion by goats (3.59% ± 0.16) than cattle (1.93% ± 0.09) and control or untreated seeds (1.69% ± 0.11). Less dense grass cover, which resulted in reduced grass competition with tree seedlings for light, space and water, and improved seed scarification due to gut passage were vital for emergence and recruitment of Acacia seedlings. These results will contribute considerably to the understanding of the recruitment phase of woody plant encroachment.